Ca2+, the endoplasmic reticulum and cardiac pathology - Michalak, Marek (Henry Stewart Talks, 2012)
Molecular studies on the endoplasmic reticulum (ER) function and ER associated chaperones including calreticulin, ER-associated functions are crucial in cardiac physiology and pathology -ER stress responses, ER calcium buffering proteins impact many cardiac functions including cardiogenesis, ischemia and reperfusion, cardiomyopathies and heart failure